Autoritarismo calculado: uma análise crítica de páginas brasileiras de direita e de esquerda no Facebook - Holanda, Rochelly Rodrigues (2020)
This study aimed to analyze traces of a potentially authoritarian mentality from Facebook users speech linked to self-declared right and left political pages in Brazil. Methodologically, Netnografia offered input for inset and participant observation in the online environment. To this purpose, the pages “Eu era Direita e não sabia” and “Jovens de Esquerda” were selected through Facebook Audience Insights (FAI), a tool used by entrepreneurs who use available sociodemographic data to improve the reach of their products on said social network. We also use Netvizz, an application that uses the Facebook programming interface to show data from pages, groups and events. Through it, eight posts were collected - four on each of the pages studied here - with greater comments engagement. Finally, 3489 comments were collected from these eight publications between August and November 2018, a period corresponding to the beginning of presidential election propaganda until the month after the second round results. These comments were organized in a textual corpus submitted to Iramuteq, a free software that allows analysis of textual data through lexicography. Comments loaded with prejudice and intolerance led the speeches analyzed in this work. Under the bias of Critical Theory, based on the immanent critical analysis of this object, are evident here aspects that concern the form of authoritarian thinking in the discursive practices in online social networks and rooted under Brazilian sociopolitical scope. As a result of this work, it is presented how the discussion of authoritarian thinking is manifested in the rationalization of contemporary society, threatening the democratic process and the construction of a plural and free society.